Examining the Role of Transmission of Chelonid Alphaherpesvirus 5 - Chaves, Andrea (2017)
Marine turtle fibropapillomatosis (FP) is a devastating neoplastic disease characterized by single or multiple cutaneous and visceral fibrovascular tumors. Chelonid alphaherpesvirus 5 (ChHV5) has been identified as the most likely etiologic agent. From 2010 to 2013, the presence of ChHV5 DNA was determined in apparently normal skin, tumors and swab samples (ocular, nasal and cloacal) collected from 114 olive ridley (Lepidochelys olivacea) and 101 green (Chelonia mydas) turtles, with and without FP tumors, on the Pacific coasts of Costa Rica and Nicaragua. For nesting olive ridley turtles from Costa Rica without FP, 13.5% were found to be positive for ChHV5 DNA in at least one sample, while in Nicaragua, all olive ridley turtles had FP tumors, and 77.5% tested positive for ChHV5 DNA. For green turtles without FP, 19.8% were found to be positive for ChHV5 DNA in at least one of the samples. In turtles without FP tumors, ChHV5 DNA was detected more readily in skin biopsies than swabs. Juvenile green turtles caught at the foraging site had a higher prevalence of ChHV5 DNA than adults. The presence of ChHV5 DNA in swabs suggests a possible route of viral transmission through viral secretion and excretion via corporal fluids.